A Link Between Mitochondrial Dysfunction and the Immune Microenvironment of Salivary Glands in Primary Sjogren’s Syndrome - Li, Ning; Li, Yusi; Hu, Jiawei; Wu, Yicheng; Yang, Jie; Fan, Hongmei; Li, Lei; Luo, Danyang; Ye, Yulin; Gao, Yiming; Xu, Haimin; Hai, Wangxi; et al. (Frontiers in Immunology, 2022)
Background：Primary Sjogren’s syndrome (pSS) is a slowly progressive, inflammatory autoimmune disease characterized by lymphocytic infiltration into salivary and lacrimal glands. It becomes more recognized that morphology alterations of epithelial mitochondria are involved in altered cellular bioenergetics in pSS patients. The integrated analysis of the mitochondrial role in the pathogenesis and aberrant immune microenvironment in pSS remains unknown. Methods: The mitochondrial-related genes and gene expression data were downloaded from MitoMiner, MitoCarta and NCBI GEO database. We performed novel transcriptomic analysis and constructed a network between the mitochondria function and immune microenvironment in pSS-salivary glands by computer-aided algorithms. Subsequently, real-time PCR was performed in clinical samples in order to validate the bioinformatics results. Histological staining and transmission electron microscopy (TEM) were further studied on labial salivary gland samples of non-pSS and pSS patients characterized for mitochondria-related phenotypic observation in the different stages of the disease. Results: The bioinformatic analysis revealed that the expression of several mitochondrial-related genes was altered in pSS. Quantitative real-time PCR showed four hub genes, CD38, CMPK2, TBC1D9 and PYCR1, were differentially expressed in the pSS clinical samples. These hub genes were associated with the degree of immune cell infiltration in salivary glands, the mitochondrial respiratory chain complexes, mitochondrial metabolic pathway in gluconeogenesis, TCA cycle, and pyruvate/ketone/lipid/amino acid metabolism in pSS. Clinical data revealed that the gene expression of fission (Fis1, DRP1 and MFF) and fusion (MFN1, MFN2 and OPA1) was down-regulated in pSS samples, consistent with the results from public validation database. As the disease progressed, cytochrome c and Bcl-2 proteins were regionally distributed in salivary glands from pSS patients. TEM revealed cytoplasmic lipid droplets and progressively swollen mitochondria in salivary epithelial cells. Conclusion: Our study revealed cross-talk between mitochondrial dysfunction and the immune microenvironment in salivary glands of pSS patients, which may provide important insights into SS clinical management based on modulation of mitochondrial function.